PENGARUH MOTIVASI, KOMITMEN DAN PELATIHAN TERHADAP KINERJA PEGAWAI (STUDI EMPIRIS PADA BKPSDM KABUPATEN KONAWE UTARA) - Yusran Adi; Ansar Taufiq; Sofian Syahrul (Perkumpulan Dosen Manajemen Indonesia, 2021)
This research was conducted with the aim of: 1) analyzing the influence of motivation on the performance of BKPSDM employees in North Konawe Regency, 2) analyzing the effect of commitment on the performance of BKPSDM employees in North Konawe Regency, 3) analyzing the effect of training on the performance of BKPSDM employees in North Konawe Regency and 4) analyzing the influence Motivation, Commitment and Training on the performance of BKPSDM employees in North Konawe Regency. This study uses primary data and secondary data. The study population was 71 employees of the North Konawe District Civil Service and Human Resources Development Agency (BKPSDM) at September 2020. The sample was 71 people’s using the sensus method. Collecting data through: observation, interviews, questionnaires and documentation. The analytical method used is multiple linear regression analysis with the SPSS programs version 23. The results of the study prove that simultaneously the motivation, commitment and training variables have a positive and significant effect on the performance of BKPSDM employees in North Konawe Regency with an F-count 63.176 with sig = 0.05. Partially the training variable has a dominant influence compared to other variables with the t value of 4.691.